Efek Penambahan Bahan Alami pada Litter Terhadap Performans dan Parameter Kesehatan Broiler - Joko Sujiwo; Bambang Ariyadi (Universitas Bengkulu, 2023)
This study investigated the impact of adding natural compounds, including zeolite, charcoal, Quicklime, and limestone, to broiler litter on broiler chickens' performance and health parameters. The experiment was conducted using a completely randomized design with five treatments: T1 = fresh rice husk without additional compound, T2 = 10% zeolite, T3 = 10% charcoal, T4 = 5% quicklime, and T5 = 5% limestone. The results showed that adding natural compounds improved broilers' growth rate, with the highest final body weight observed in the T5, 2459.78 g. Mortality rates did not differ significantly among treatments. The addition of natural compounds did not affect (P > 0.05) the relative weight of the immune organ, except the liver. The addition of natural compounds did not significantly affect blood parameters, including red blood cell count, white blood cell count, and haemoglobin levels (P > 0.05). Additionally, the incidence of footpad dermatitis was lower in litter treated with natural compounds than in untreated litter. In conclusion, adding natural compounds to broiler litter can enhance broiler performance and health without adverse effects, promoting overall growth and reducing footpad dermatitis.